Effects of Meditation on Stress Levels of Physical Therapist Students. Issue 3 (2016) - Chambers, Joshua; Phillips, Beth; Burr, Michael; Xiao, Danny
Abstract : Background and Purpose. : Due to the arduous nature of the professional (entrylevel) physical therapist (PT) education program, PT students often experience higher levels of stress than their age and gender‐matched peers, which can negatively affect their academic performance and wellbeing. Therefore, finding methods to manage stress is important for students' wellbeing and academic success. The purpose of this study was to investigate the effect of meditation on stress levels of students in a doctor of physical therapy program. Participants. : Twenty‐four PT students in their first and second year of an entry‐level doctoral degree program participated in this study. Methods. : This study examined the stress levels of 24 subjects via blood pressure, morning and evening salivary cortisol levels, and 3 different stress questionnaires (Perceived Stress Scale, General Anxiety Disorder 7, Stress Visual Analog Scale) using a quasi‐experimental pretest‐posttest design. The intervention was a twice‐daily 20‐minute beeja mantra‐based meditation performed for 8 weeks. Results. : All 24 students completed the study with average compliance of 91.6% ± 8.7% (mean ± SD) meditating at least once per day, and 77.3% ± 19.8% meditating twice per day. A paired t test was used to analyze the blood pressure readings, with systolic blood pressure decreasing by 2.9 ± 2.3 (standard error of the mean: SEM) mmHg ( P = .022), and diastolic blood pressure decreasing by 4.6 ± 2.9 (SEM) mmHg ( P = .005). Four subjects with prehypertensive systolic blood pressure readings prior to the meditation intervention moved into healthy normal range by the conclusion of the study. The Wilcoxon signed rank test was used to evaluate the questionnaires, which showed significantly decreased subjective stress levels ( P < .05). No significant changes in mean morning (AM) or night (PM) salivary cortisol levels were found ( P > .05). However, 9 of the 14 (64%) subjects who had at least 1 cortisol measurement outside of the normal range (established by ZRT Labs) at the start of the study had both AM and PM cortisol levels in the normal range following the intervention. Discussion and Conclusion. : The results of this study show that an 8‐week mantrabased meditation program significantly reduces blood pressure, significantly reduces perception of stress based on the subjective questionnaires, and that a 1‐day AM/PM cortisol sample may not be sufficient to accurately analyze a subject's true daily cortisol level to show statistical change.